A molecular dynamics study on the CO2 permeability of microalgae lipid membrane - Manrique, Robby (Animo Repository, 2020)
Reducing the amount of carbon emissions has been a formidable challenge especially to countries experiencing rapid economic growth. This prompted the development of various materials and methodologies to capture emissions to address climate change. The current study aimed to contribute in the development of carbon dioxide capture through the biological approach by using microorganisms such as microalgae. Biological fixation involving microalgae involves a complex process that has not been fully understood as current experimental methods can only deliver analysis on a macroscopic scale. The study demonstrated the dynamics of carbon dioxide molecules in the atomic scale using molecular dynamics. The permeation coefficient of carbon dioxide molecules was calculated at different range of temperature and salinity using the inhomogeneous solubility diffusion model. The GROMOS53a6 and SPC force field was used for the interaction of molecules. Moreover, the force autocorrelation function was used to calculate the diffusion coefficient. The resulting diffusion coefficients were in a good agreement with experimental data. The highest permeation coefficient of 2.3994 × 10−3 cm s−1 was calculated at 330 K 0.55 M conditions. Due to the nonpolar nature of carbon dioxide molecule, the mobility as it permeates inside the bilayer was not affected. Hence, the study suggests that the temperature and salinity does not prevent nor significantly affects the permeability of microalgae lipid membrane from carbon dioxide molecules. © 2019, Springer Nature B.V.